(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Interview via Skype by the actress and director Quitéria Kelly of the Carmin Group, on January 27, 2019, about the shows Jacy and A Invenção do Nordeste. The interview arose from my interest in documentary theater, and addresses two pieces of aesthetics from the Carmin Group Documentary Theater.